2006
DOI: 10.1080/09513590601010557
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychological symptoms in Greek postmenopausal women: Association with hormone therapy

Abstract: Quality of life (QoL) in menopause is influenced by many parameters, including vasomotor symptoms, psychological status and culture. The aim of the present study was to examine the association of hormone therapy (HT) with QoL and psychological symptoms in Greek postmenopausal women. The study assessed 216 postmenopausal women (mean age 54.5 years) attending a university menopause clinic in Greece. Fifty-three were users of HT and 163 were not. QoL was evaluated by the Utian Quality of Life Scale (UQOL) and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
4
6
0
1
Order By: Relevance
“…Highly educated women were also more likely to answer that they had good QOL; similar to the findings of other studies (Koundi et al, 2006;Abourazzak et al, 2009). All the domains showed that the higher the qualification, the higher the WHOQOL-BREF QOL scores.…”
Section: Discussionsupporting
confidence: 87%
“…Highly educated women were also more likely to answer that they had good QOL; similar to the findings of other studies (Koundi et al, 2006;Abourazzak et al, 2009). All the domains showed that the higher the qualification, the higher the WHOQOL-BREF QOL scores.…”
Section: Discussionsupporting
confidence: 87%
“…Conde et al [7] noted that age, marital status, and parity were not related to the QoL. In a study conducted by Koundi et al [11], while education, number of children, and marital status showed an effect on some dimensions of QoL, age, and years since menopause did not predict QoL in postmenopausal women. In our sample, lower economical and educational levels appeared to be more connected with impaired QoL compared to other sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 96%
“…Severity of disease, physical image of oneself and one’s response to problems are among the factors affecting the quality of life. Also, vulvovaginal atrophy is associated with urinary symptoms such as dysuria, nocturia, frequency, recurrent urinary tract infections, and incontinence (34). In this study, treatment with royal jelly and Premarin improved psychological status in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%